Smart Stick Using iBeacon For Visually Impaired Person - Dnyaneshwar, Bhawar Kajal (Journal of Advanced Research in Signal Processing and Applications, 2021)
The visually impaired community depends on seeing people for a significant amount of info and assistance. This project, explores the ability of iBeacon technology to support visually impaired people though circumnavigating in the open. Testing exposed that the current iBeacon system coupled with the necessary Bluetooth technology, provides voice notification that can be used for assistance for blind people. Interviews with industry experts revealed that the weaknesses have been overcome internationally by blending Bluetooth with other technologies. Hence, that iBeacons have great potential as an assistive tool for visually impaired people. How to cite this article: Dnyaneshwar BK, Kharjul PS, Arjun PA et al. Smar Stick using iBeacon for Visually Impaired Person J Adv Res Sig Proc Appl 2019; 1(2): 20-23